Hell's half-acre: the untold story of the Benders, a serial killer family on the American Frontier - Jonusas, Susan (Viking, 2022)
"In 1873 the people of Labette County in Kansas made a grisly discovery. Buried on a homestead seven miles south of the town of Cherryvale, in a bloodied cellar and under frost-covered soil, were countless bodies in varying states of decay. The discovery sent the local community and national newspapers into a frenzy that continued for over two decades, and the land on which the crimes took place became known as 'Hells Half-Acre.' When it emerged that a family of four known as the Benders had been accused of the slayings, the case was catapulted to infamy. The idea that a family of seemingly respectable homesteaders--one among thousands who were relocating further west looking for land and opportunity after the Civil War--were capable of operating 'a human slaughter pen' appalled and fascinated the nation. But who the Benders really were, why they committed such a vicious killing spree, and what became of them when they fled from the law is a mystery that has remains unsolved to this day--not that there aren't some convincing theories. Part gothic western, part literary whodunnit, and part immersive study of postbellum America, Hell's Half-Acre sheds new light on one of the most notorious cases in our nation's history while holding a torch to a society under the strain of rapid change and moral disarray. Susan Jonasus draws on extensive original archival material, and introduces us to a fascinating cast of characters, including the despairing families of the victims as well as the fugitives that helped the murderers escape. Hell's Half-Acre is not simply a book about a mass murder. It is a journey into the turbulent heart of nineteenth century America, a place where modernity stalks across the landscape, violently displacing existing populations and wearily building new ones. It is a world where folklore can quickly become fact, and an entire family of criminals can slip right through a community's fingers, only to reappear at the most unexpected of times"--